The Innovative Role of Tri Alam Lestari Waste Bank in Environmental Management - Grace Prima (Journal of Sumatera Sociological Indicators, 2025)
Waste pollution is still a classic problem that plagues Indonesia from all corners of the region. The functioning of each element in the social life of the community is an important component in maintaining environmental stability. Therefore, this research aims to understand the relationship between the environment and people. This study also discusses the role of humans in environmental management. The research method used in this research is qualitative, where data is obtained through literature studies, which are then analysed using the functional structural perspective analysis knife. The study in this discussion presents the Tri Alam Lestari Waste Bank as an interesting object of study to be researched. The results of this study show that the functioning of an element in the web of life can influence each other. Tri Alam Lestari Waste Bank and the surrounding community have carried out environmental conservation practices, which are then considered in the functional structural perspective as the functioning of an element of life. Keyword: Waste, Environment, Humans, Function